Effect Of Avocado Seed (Persea Americana Mill.) On The Growth Of Bacteria Prevotella Intermedia (In Vitro) - Syifaul Amrodi Al Birro; Nur Ariska Nugrahani; Nina Runting; Noor Hafida Widyastuti (Sean Institute, 2023)
Periodontitis is an inflammatory disease of the supporting tissues of the teeth caused by bacteria present in the dental plaque biofilm. Gingivitis and periodontitis are the most common periodontal diseases and are associated with bacteria Prevotella intermedia. Avocado seeds are one way to inhibit this bacteria. the aim of this study is to prove that avocado seed extract (Persea americana Mill.) has an antibacterial effect on bacterial growth Prevotella intermedia. This study was a pure laboratory experimental post-test only control group design. The research sample was divided into 10 groups, namely 8 groups of avocado seed extract with different concentrations, 1 positive control group (chlorhelxidinel glulconat 0,2%), and 1 negative control group (aquades). Avocado seed extract (Persea americana Mill.) has antibacterial power against bacteria Prevotella intermedia with Minimum Inhibitory Concentration (MIC) of 3.125% and Minimum Bactericidal Concentration (MBC) of 6.25%. Avocado seed extract has antibacterial power against the bacteria Prevotella intermedia with MIC 3.125% and MBC 6.25%.